Fertilizing Trees and Shrubs - Nighswonger, James J. (My University, 1992)
Fertilization can result in more rapid growth; faster recovery from injury, pruning, or pest problems; improved health and better foliage color.
L707_1992-10
Keywords: L707; Environment and Natural Resources; Lawn and Garden; Forestry; L